2022
DOI: 10.3389/fimmu.2022.898039
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of the NLRP3 Inflammasome Pathway in Acute Intestinal Inflammation: Use of THP-1 Knockout Cell Lines in an Advanced Triple Culture Model

Abstract: The NLRP3 inflammasome plays an important role in intestinal homeostasis as well as inflammation. However, in vivo studies investigating the role of the NLRP3 inflammasome in inflammatory bowel disease (IBD) report contrasting results, leaving it unclear if the NLRP3 inflammasome augments or attenuates intestinal inflammation. To investigate the role of the NLRP3/caspase-1 pathway in a model of acute intestinal inflammation, we modified a previously established in vitro triple culture model of the healthy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Among a variety of inflammasome, NLRP3 inflammasome composed of NLRP3, ASC and pro-caspase-1 is the most widely investigated (Mangan et al, 2018). The NLRP3 inflammasome plays a vital role in regulating the inflammatory response in the intestines and maintaining homeostasis by mediating multiple pro-inflammatory signals (Busch et al, 2022;Martinez-Lopez et al, 2022). After stimulation, NLRP3 recruits ASC adaptor to accelerate the recruitment of procaspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…Among a variety of inflammasome, NLRP3 inflammasome composed of NLRP3, ASC and pro-caspase-1 is the most widely investigated (Mangan et al, 2018). The NLRP3 inflammasome plays a vital role in regulating the inflammatory response in the intestines and maintaining homeostasis by mediating multiple pro-inflammatory signals (Busch et al, 2022;Martinez-Lopez et al, 2022). After stimulation, NLRP3 recruits ASC adaptor to accelerate the recruitment of procaspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…Busch et al (2021) suggested that this advanced in vitro triple-culture model was a promising approach for studying the toxicological effects of ingested micro- and nano-plastic particles [ 80 ]. An adverse and pro-inflammatory role of the NLRP3 inflammasome in IBD has been described by using this triple-culture model [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among a variety of inflammasome, NLRP3 inflammasome composed of NLRP3, ASC and pro-caspase-1 is the most widely investigated ( Mangan et al, 2018 ). The NLRP3 inflammasome plays a vital role in regulating the inflammatory response in the intestines and maintaining homeostasis by mediating multiple pro-inflammatory signals ( Busch et al, 2022 ; Martinez-Lopez et al, 2022 ). After stimulation, NLRP3 recruits ASC adaptor to accelerate the recruitment of pro-caspase-1.…”
Section: Discussionmentioning
confidence: 99%